Big data? qualitative approaches to digital research - Hillyard, Sam.; Hand, Martin, 1971- (Bingley, U.K. : Emerald, 2014)
This volume seeks to address the emerging relationships between qualitative research and digital data. At the present time, ubiquitous digital data is altering the foci of research, the contexts in which research takes place, and the methods and tools available for qualitative research. Alongside new challenges and opportunities, there are many ways in which established qualitative methods are being used to situate and interpret digital phenomena. This book examines and engages with the ambivalence of digitization, illuminating the diverse ways in which researchers approach, negotiate, understand and interpret objects and practices of digital research. The chapters in this volume are organized around four key themes: researching impacts of digitization on social worlds; researching uses of digital data within social worlds; researching digital visualization of social worlds; researching with digital data and methods. The volume is designed to appeal to qualitative researchers seeking to study processes of digitization, adjust existing methodologies for digital worlds, and develop new ways of examining and using digital research.
From cyberspace to the dataverse : trajectories in digital social research / Martin Hand -- Politics, policy and privatisation in the everyday experience of big data in the NHS / Andrew Goffey, Lynne Pettinger, Ewen Speed -- Big data ambivalence : visions and risks in practice / Daniel Trottier -- The researcher and the never-ending field : reconsidering big data and digital ethnography / Christine Lohmeier -- Researching forums in online ethnography : practice and ethics / Emma Hutchinson -- Marketing narratives : researching digital data, design and the in/visible consumer / Mariann Hardey -- Not being there : research at a distance with video, text and speech / Angus Bancroft ... [et al.] -- Using software for qualitative data analysis : research outside paradigmatic boundaries / Jonathan Tummons -- Missed miracles and mystical connections : qualitative research, digital social science and big data / Robin James Smith -- Digitization and memory : researching practices of adaption to visual and textual data in everyday life / Martin Hand -- 'Where no-one can hear you scream' : an analysis of the potential of 'big data' for rural research in the British context / Sam Hillyard -- Investigating the other : considerations on multi-species research / Nik Taylor, Lindsay Hamilton.
Print version record
Keywords: Social Science -- Statistics; Social Science -- Methodology; Social Science -- Sociology -- General; Sociology; Big data; Qualitative research -- Methodology; Digital media